Pelosi's intoxication of Taiwan and democrat's flopped performance in the US midterm election - Hasija, Namrata (Penerbit Universiti Kebangsaan Malaysia, 2022)
Although traditionally, flopped performance of the Democrats in the US mid-term elections and Pelosi's failure to retain the majority of the house is expected, many analysts do not rule out the possibility of an increased significant connection between the development between the US election and events in the international politics. Therefore, it is highly likely for Taiwan to consider foreign policy options without US security protection in the face of China's threat under President Xi Jinping's third term is inevitable. This brief commentary provides views to answer some of the following questions: What is the most important international security lesson since the incident of Nancy Pelosi's visit as the former Leader of the United States (US) Congress to Taiwan last August 2022? How does the increasing tension in relations between Beijing and Washington foreshadow Taiwan's security future as it becomes increasingly dark and uncertain from the possible invasion of Mainland China?